HIV-related stigma and discrimination: a study of health care workers in Banda Aceh, Indonesia (Medical Journal of Indonesia, 2013)
Background: The aim of this study was to identify the level of stigmatized and discriminatory attitudes towards people living with HIV (PLHIV) among health care workers (HCWs) and the factors that influenced these attitudes. Methods: This research was conducted at Dr. Zainoel Abidin General Hospital Banda Aceh, Indonesia. A cross-sectional study design was adopted for this research. Eighty nine HCWs were included in this study and they were selected purposively. Correlation analysis, analysis of variance and independent sample t test analysis was used according to the type of data. Finally, a multiple linear regression model was used to identify the predictor factor for stigmatized and discriminatory attitudes. Results: We found that the level of stigmatized and discriminatory attitudes was high. Bivariate analysis showed that type of HCW, education, marital status, knowledge on transmission and prevention of HIV and irrational fear of HIV transmission were significant related with stigmatized attitudes (p < 0.05). Type of HCW, marital status, age, knowledge on transmission and prevention of HIV and irrational fear of HIV transmission indicated significant (p < 0.05) differences in the levels of discriminatory attitudes. A multiple linear regression model identified type of HCW and irrational fear of HIV transmission correlated with stigmatized attitudes (R2 = 0.230) and knowledge on transmission and prevention of HIV correlated with discriminatory attitudes (R2 = 0.119). Conclusion: Irrational fear of HIV transmission and type of HCW are significant predictors to stigmatized attitudes; knowledge on transmission and prevention of HIV is a predictor to discriminatory attitudes towards PLHIV among HCWs. (Med J Indones. 2013;22:22-9) Keywords: Discrimination, discriminatory attitudes, HIV, PLHIV, stigmatized attitudes.